Organizational Intelligence and Market Expansion in Jordanian Pharmaceutical Companies - Najm, Najm A.; Alfaqih, Amany A. H. (Organizations and Markets in Emerging Economies, 2021)
There are many studies that have focused on the Albrecht model of organizational intelligence (OI) and its seven dimensions (strategic vision, shared fate, appetite for change, heart, alignment and congruence, knowledge deployment, and performance pressure), but the current study presents a new attempt to study OI using the Yolles model in its three dimensions (self-reference, self-regulation, and self-organization) (2005). This study sought to determine the effect of organizational intelligence on market expansion (new markets and new product) in the Jordanian pharmaceutical industry, and it examined the effect of transformational leadership as a mediating variable on the relationship between organizational intelligence and market expansion. The study sample consisted of 231 respondents taken from six pharmaceutical companies divided into three categories according to their size as small, medium and large companies. The results confirmed that there is a significant positive effect of the two dimensions (self-regulation and self-organization) on new markets, while three dimensions of OI have a significant effect on new products in the pharmaceutical companies.